2012
DOI: 10.1088/0967-3334/33/2/259
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based motion artifact removal for functional near-infrared spectroscopy

Abstract: Functional near-infrared spectroscopy (fNIRS) is a powerful tool for monitoring brain functional activities. Due to its non-invasive and non-restraining nature, fNIRS has found broad applications in brain functional studies. However, for fNIRS to work well, it is important to reduce its sensitivity to motion artifacts. We propose a new wavelet-based method for removing motion artifacts from fNIRS signals. The method relies on differences between artifacts and fNIRS signal in terms of duration and amplitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
357
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(359 citation statements)
references
References 31 publications
1
357
0
1
Order By: Relevance
“…It has been found that wavelet methods compare favorably to other methods for the correction of motion artifacts in single-channel NIRS time series [9], [21], [24]. Fig.…”
Section: E Wavelet-based Artifact Reductionmentioning
confidence: 92%
See 3 more Smart Citations
“…It has been found that wavelet methods compare favorably to other methods for the correction of motion artifacts in single-channel NIRS time series [9], [21], [24]. Fig.…”
Section: E Wavelet-based Artifact Reductionmentioning
confidence: 92%
“…However, if artifacts differ substantially among channels or if multiple channels are unavailable, then single-channel methods are needed [9], [21], [24]. Several methods for detecting and/or correcting motion artifacts in NIRS time series have been compared [9], [21], [24], [31], [32], leading to the conclusion that wavelet-based methods are more effective than other methods, especially for single-channel processing. Wavelets have also been shown effective for reducing ocular artifacts in EEG [2], [22].…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods remove MAs by examining the characteristics of the signal [26][27][28][29][30][31][32][33]. One of these methods was developed by our group, the "movement artifact reduction algorithm" (MARA) [34].…”
Section: Introductionmentioning
confidence: 99%